Ionic Solids: Introduction, General Aspects - Mora Veera Madhava Rao (Ionic Solids: Introduction, General Aspects, 2021)
This book reviews the introduction of ionic solids. The transport phenomena in the solid state are of equal importance in basic research and potential applications. The particular interest has been directed towards ionic solids because of their attractive electric-power applications. Ionic conduction is an essential process in many solid-state reactions. Ionic conductors have different microstructure and physical properties. Solid ionic conductors are generally classified into four types of phases: open channel structures, amorphous-glassy electrolytes, polymer electrolytes and composite electrolytes. Each has important applications with different fabrication requirements.